Corrosion investigations of Al-Si casting alloys in 0.6 M NaCl solution - Smokvina Hanza, Sunčana (Array, 2021)
This paper presents results of the corrosion investigations of specimens made from finished parts for the automotive industry, produced by high-pressure die casting and gravity die casting process of six Al-Si alloys (40000 series). Open circuit potential and potentiodynamic polarization measurements have been performed using a potentiostat with three-electrode set-up in 0.6 M NaCl naturally aerated solution. Microstructural characterization before and after electrochemical investigations has been carried out with optical microscope to establish the connection between microstructure and corrosion parameters of investigated alloys and to analyze and record surface changes of each sample due to electrochemical corrosion. All alloys show good corrosion resistance, which manifests with low values of corrosion rates, calculated from the corrosion current densities obtained from potentiodynamic polarization measurements. Differences in electrochemical behavior appear due to the distinctions in their chemical composition and microstructure. The type of casting process does not affect electrochemical behavior of Al-Si alloys.